Psychological treatments in schizophrenia: I. Meta-analysis of family intervention and cognitive behaviour therapy. - Pilling, S; Bebbington, P; Kuipers, E; Garety, P; Geddes, J; Orbach, G; Morgan, C (2002)
BACKGROUND: While there is a growing body of evidence on the efficacy of psychological interventions for schizophrenia, this meta-analysis improves upon previous systematic and meta-analytical reviews by including a wider range of randomized controlled trials and providing comparisons against both standard care and other active interventions. METHOD: Literature searches identified randomized controlled trials of four types of psychological interventions: family intervention, cognitive behavioural therapy (CBT), social skills training and cognitive remediation. These were then subjected to meta-analysis on a variety of outcome measures. This paper presents results relating to the first two. RESULTS: Family therapy, in particular single family therapy, had clear preventative effects on the outcomes of psychotic relapse and readmission, in addition to benefits in medication compliance. CBT produced higher rates of 'important improvement' in mental state and demonstrated positive effects on continuous measures of mental state at follow-up. CBT also seems to be associated with low drop-out rates. CONCLUSIONS: Family intervention should be offered to people with schizophrenia who are in contact with carers. CBT may be useful for those with treatment resistant symptoms. Both treatments, in particular CBT, should be further investigated in large trials across a variety of patients, in various settings. The factors mediating treatment success in these interventions should be researched.